Opioid analgesic prescribing and use – an audit of analgesic prescribing by general practitioners and The Multidisciplinary Pain Centre at Royal Brisbane Hospital - Nissen, L M (Blackwell Science Inc, 2001)
AIMS: This study evaluated the use of and need for opioids in patients attending the Multidisciplinary Pain Centre at the Royal Brisbane Hospital (RBH). METHODS: All consecutive in-patient admissions in 1998 were reviewed. A 10-point scoring system based on the World Health Organization (WHO) analgesic ladder was devised to facilitate comparison of analgesic prescribing on admission and at the time of discharge. A conversion table was used to standardize opioid analgesic doses to an oral morphine equivalent. RESULTS: Of the 370 patients reviewed, 233 (81%) were by their general practitioners. Records of 288 (78%) were available for full review and 270 (94%) of these had noncancer pain. On admission, 239 (83%) were taking an opioid analgesic, with 135 (47%) taking strong opioids (e.g. morphine, oxycodone, methadone). There was a significant decrease in the mean total daily oral morphine equivalent prescribed on discharge 36.9 mg (95% CI: 33.4, 40.4) compared with that on admission 88.7 mg (95% CI: 77.6, 99.8) (P < 0.001). There was a significant decrease (P < 0.05) in the proportion of patients taking a primary opioid on discharge 153 (58%) compared with admission 239 (83%), although the proportion of patients taking a strong opioid on discharge 150 (52%) compared with admission 135 (47%) was not significantly different (P > 0.05). The proportion of patients taking a laxative showed a significant increase on discharge 110 (73%) compared with admission 38 (28%) (P < 0.05). CONCLUSIONS: Our analgesic prescribing scoring system and opioid conversion table have the potential to be developed further as tools for assessing opioid analgesic prescribing. The significant decrease in total daily oral morphine equivalents signifies the value of prescribing in accordance with the WHO analgesic ladder, and the necessity of general practitioner education. The management of chronic pain is complex, and it requires interventions additional to pharmacological therapy. Evaluation by a multidisciplinary team, coupled with experience in and an understanding of analgesic prescribing and rehabilitation provides an effective basis for improving the management of patients with chronic pain.